Thermally conductive cyanate ester nanocomposites filled with graphene nanosheets and multiwalled carbon nanotubes. (22nd September 2014) - Zhao, Chunbao; Xu, Suichun; Qin, Yufang; Chen, Hexiang; Zhao, Wei; Sun, Fengmei; Zhu, Xianzhong
<x xml:space="preserve">Abstract</x> In this work, dodecylamine‐modified graphene nanosheets (DA‐GNSs) and γ‐aminopropyl‐triethoxysilane‐treated multiwalled carbon nanotubes (f‐MWCNTs) are employed to prepare cyanate ester (CE) thermally conductive composites. By adding 5 wt% DA‐GNSs or f‐MWCNTs to the CE resin, the thermal conductivities of the composites became 3.2 and 2.5 times that of the CE resin, respectively. To further improve the thermal conductivity, a mixture of the two fillers was utilized. A remarkable synergetic effect between the DA‐GNSs and f‐MWCNTs on improving the thermal conductivity of CE resin composites was demonstrated. The composite containing 3 wt% hybrid filler exhibited a 185% increase in thermal conductivity compared with pure CE resin, whereas composites with individual DA‐GNSs and f‐MWCNTs exhibited increases of 158 and 108%, respectively. Moreover, the composite with hybrid filler retained high electrical resistivity. Scanning electron microscopy images of the composite morphologies showed that the modified graphene nanosheets (GNSs) and multiwalled carbon nanotubes (MWCNTs) were uniformly dispersed in the CE matrix, and a number of junction points among MWCNTs and between MWCNTs and GNSs formed in the composites with hybrid fillers. Generally, we can conclude that these composites filled with hybrid fillers may be promising materials of further improving the thermal conductivity of CE composites. Copyright © 2014 John Wiley & Sons, Ltd.